Hipoteks sejarah dalam novel Panglima Awang - Mawar Shafei, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
This article focuses on the concept of ‘intertext’ in Harun Aminurrashid’s novels. The concept appears in Malay literary tradition for example in lipurlara, manuscript writing and the novel itself. This tendency relates to ‘intertextuality’ as a phenomenon on the existence of ‘a text within a text’ or ‘dialogue between texts’. Julia Kristeva coined the term ‘intertextuality’ in her readings of the work of Mikhail Mikhailovich Bakhtin and Ferdinand de Saussure’s sign system and later followed by several scholars such as Roland Barthes, Gerard Genette, Michael Riffaterre and Harold Bloom. Harun Aminurrashid demonstrates his inclination towards historical themes and settings through his novels such as Darah Kedayan, Jong Batu, Siapakah Bersalah?, Sebelum Ajal, Merebut Gadis Jelita, Wak Cantuk, Panglima Awang and Anak Panglima Awang. Explicitly, Panglima Awang, portrays its intertextuality with the historical elements. The hypotexts incorporated several articles on the Portuguese in Malacca and Ferdinand de Magalhaes @ Magellan’s circumnavigation. Some intertextual processes involve transformation, modification and demitefication. Intertextuality could be said to denote authorship strategy, reflecting an attempt to ‘modify’ history to channel Malay aspirations and the spirit to uphold the self-worth of the Malays